Comparative analysis of mycorrhizal communities associated with Struthiopteris spicant (L.) Weiss across Europe and North America - Guillen-Otero, Thais; Hertel, Dietrich; Quintanilla, Luis G.; Lehnert, Marcus; Schmid, Mattia; Kharazishvili, Davit; Fawcett, Susan; Kessler, Michael (Frontiers in Plant Science, 2024)
Ferns constitute the second largest group of vascular plants. Previous studies have shown that the diversity and composition of fern communities are influenced by resource availability and water stress, among other factors. However, little is known about the influence on these environmental factors on their biotic interactions, especially regarding the relationship between mycorrhizal fungi and ferns. The present study compares the mycorrhizal communities associated with 36 populations of Struthiopteris spicant L. Weiss across Europe and North America. This species exhibits a great tolerance to variations in light, nutrient, and pH conditions, and it can survive with and without mycorrhizae. With the aim of determining which environmental factors impact the composition and abundance of the root-associated fungal communities in this species, we used an ITS-focused metabarcoding approach to identify the mycorrhizal fungi present and analyzed the influence of climatic and edaphic variables at global and regional scales. We encountered striking differences in the relative abundance of arbuscular mycorrhizal fungi (AMF) between S. spicant populations at both spatial levels. We recorded a total of 902 fungal ASVs, but only 2-4% of the total fungal diversity was observed in each individual, revealing that each fern had a unique fungal community. Light availability and the interactive action of pH and soil nitrogen concentration showed a positive influence on AMF relative abundance, explaining 89% of the variance. However, environmental factors could only explain 4-8% of the variability in AMF community composition, indicating that it might be determined by stochastic processes. These results support the hypothesis that ferns may be more independent of mycorrhization than other plant groups and interact with fungi in a more opportunistic manner.